Autoeficacia y su relación con la permanencia-deserción en la Universidad de la Costa (2015)
The college dropout is one of the main problems of higher education worldwide has implications for economic development given the role that universities and professional play in this. The objective of this research is to establish the efficacy and its relationship to stay in college-dropout Coast in Barranquilla. The population consisted of students enrolled in the institution for the period 2015-1 and the sample was 322 students, of which 195 were active and 127 in desertion. Framed on empirical-analytical paradigm, a work of quantitative nature and cross non-experimental design was used as the Self-Efficacy Scale General (EAG) instrument, with the support of corporate information system (SICUC) from the Admissions Department and Registration. The study found that there is no significant correlation between self-efficacy and permanence, nor between self-efficacy and attrition. However, a significant finding of this study was to demonstrate that the average self-efficacy in dropouts was higher than that of students who remained in the institution.